A gender-comparative exploration of women’s and men’s pathways to prison in Thailand - Russell, Tristan (The Australian and New Zealand journal of criminology, 2020)
In feminist criminology, there is a growing body of research exploring gendered pathways into prison. However, this research has focussed predominantly on women. There are few gender comparative studies. Further, most feminist pathways research is western centric having, for the most part, been undertaken in the United States. Utilising categorical principal components analysis alongside descriptive statistics and illustrative case study examples, this paper adds to the feminist pathways research by describing and comparing women’s and men’s pathways to prison in Thailand. Three common pathways to prison emerged for both women and men: (1) peer group association/deviant lifestyle, (2) harmed and harming, (3) economically motivated. However, gendered variance was found within these common pathways. Further, two pathways emerged exclusively for women: (1) adulthood victimisation and dysfunctional intimate relationships, (2) naivety and deception. These results substantiate the notion that trajectories into prison are gendered, add empirical support to the feminist pathways perspective beyond the west, contribute to knowledge on how both women and men come to be in prison in Thailand, and in doing so, have utility for the development of gender-informed prison policies, and practices as per the United Nations Rules for the Treatment of Women Prisoners and Non-Custodial Measures for Women Offenders (the Bangkok Rules).